The development of a generic servitization systems framework. (November 2015) - Weeks, Richard; Benade, Siebert
Abstract: Manufacturing institutions are increasingly adopting and implementing a servitization strategy directed at enhancing their revenue streams and gaining a competitive advantage in a highly competitive and extremely turbulent marketplace. The focus of this paper is directed at gaining an understanding of (1) the various interactive systems that assume relevance in the creation and execution of the servitization strategy and (2) the development of a generic servitization systems framework. A multidisciplinary literature review was undertaken in order to identify the systems concerned and develop a generic servitization framework that could serve as a source of reference and information in strategy development and operational execution. Supporting evidence as to the relevancy of the model was obtained from a case study analysis conducted at a South African manufacturing institution that had implemented a servitization strategy. An important finding that emerged from the research study was that the institution's business model needed to be adapted, a process that necessitated an understanding of the respective systems involved, their interaction, and the change management difficulties encountered therein. The generic servitization framework was found to assume relevance in this regard. It is contended that the servitisation systems framework could serve as a source of reference and information for executives, management practitioners and technologists involved in similar projects. Highlights: Various interactive systems relevant to the creation and execution of a servitization strategy are identified during a literature review. A generic servitization systems framework depicting the primary product and services value chains and the support systems is proposed. The framework could serve as a source of information and reference for practitioners attempting to formulate and execute a servitization strategy. The framework has been successfully used at a manufacturer of security systems in South Africa.